Meta Consent – A Flexible Solution to the Problem of Secondary Use of Health Data - Ploug, Thomas; Holm, Søren 1901-1971 (2016)
In this article we provide an in-depth description of a new model of informed consent called ‘meta consent’ and consider its practical implementation. We explore justifications for preferring meta consent over alternative models of consent as a solution to the problem of secondary use of health data for research. We finally argue that meta consent strikes an appropriate balance between enabling valuable research and protecting the individual.
Keywords: Informed Consent; broad consent; health data; meta consent; specific consent